2018
DOI: 10.1111/jphp.12892
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms of HTR2C, LEP and LEPR on metabolic syndromes in patients treated with atypical antipsychotic drugs

Abstract: Therefore, HTR2C genetic variants may be involved in the susceptibility to MS in patients treated with atypical antipsychotics. Additionally, there was a gender effect in the presence of MS. No effect of LEP or LEPR polymorphisms or the combination of HTR2C-LEP and HTR2C-LEPR was observed for the presence of MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 32 publications
(37 reference statements)
0
10
0
Order By: Relevance
“…Gender based differences in the effects of the long-term use of antipsychotics were noticed in this study; specifically, male patients experienced a significant development of four metabolic syndrome criteria. Genetic- and gender-based differences in the effects of SGAs have previously been reported [46]. Plasma concentration of antipsychotic drugs has shown to produce varied results based on age and gender.…”
Section: Discussionmentioning
confidence: 99%
“…Gender based differences in the effects of the long-term use of antipsychotics were noticed in this study; specifically, male patients experienced a significant development of four metabolic syndrome criteria. Genetic- and gender-based differences in the effects of SGAs have previously been reported [46]. Plasma concentration of antipsychotic drugs has shown to produce varied results based on age and gender.…”
Section: Discussionmentioning
confidence: 99%
“…An association between MetS and HT2RC has also been proposed in other studies. For example, the rs498177 variant showed a significant association with MetS in female patients treated with olanzapine or risperidone [168], and the same was found for the rs518147CC and rs12836771GG variants in patients [169]. Although the contribution of HT2RC to MetS can be because of AIWG, we cannot rule-out the dysregulation of glucose metabolism.…”
Section: New Insights Into the Molecular Mechanisms By Which Sgas mentioning
confidence: 98%
“…A number of studies have found that the mutation of HTR2C is correlated with AIWG. [3][4][5][6] The -759 C/T polymorphism is located at the promoter region of HTR2C and associated with the ability to bind the transcription factor, affecting the expression of gene production. 21 This article has unprecedentedly used the complete Chinese database and conducted analyses on the correlation between HTR2C-759C/T and AIWG by using evidence-based medicine methods.…”
Section: Main Findingsmentioning
confidence: 99%
“…Furthermore, 5-HT2CR-deficient mice adopted an abnormal control of feeding behaviour, resulting in obesity and hyperglycaemias. [4][5][6] Taken together, previous genetic studies have found that a constellation of single-nucleotide polymorphisms in HTR2C is related to AIWG; the relationship between the -759 C/T (rs3813929) polymorphism and AIWG is an active field of research, but the results are controversial. Two earlier metaanalyses 7 8 ignored a number of studies in China; therefore, we performed a metaanalysis applying both English and Chinese databases to assess whether HTR2C -759 C/T is associated with AIWG.…”
Section: Introductionmentioning
confidence: 99%